Dampak Stigma Masyarakat Bagi Keluarga Yang Belum Memiliki Anak di Desa Sungai Besar Kabupaten Lingga - Erika Irmawati Putri; Nanik Rahmawati; Rahma Syafitri (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2023)
A woman's nature is to conceive and give birth. So when they get married they are required to have children. When they do not have children, there are stigmas that society gives to these women without seeing the cause. Such as barren women and less perfect women. This is called prejudice because it is not based on adequate knowledge, experience or evidence. Such conditions are inseparable from the social construction of women's gender roles, when a woman does not get pregnant, she will be stigmatized and reprimanded by family and society. Society will more often give a negative label to married couples who do not have children, especially to women who are the center of motherhood without seeing the causal factors or conditions that are being experienced by the married couple. In this study, researchers used qualitative research, with the research location in Sungai Besar Village, Lingga Regency. Determination of informants by pupose sampling, namely a sample that is chosen deliberately by considering that the selected informants are considered capable of providing the information needed. The informants in this study totaled sixteen informants, informants from married couples who did not have children, families and the community of Sungai Besar Village, Lingga Regency. This research was conducted to find out the impact of community stigma for married couples who do not have children. The theory used in this study is the theory of stigma by explaining the form of stigma and self-concept and the view of society by Erving Goffman. The results showed that there is an impact of community stigma for married couples who do not have children in Sungai Besar Village, Lingga Regency. Community stigma is inseparable from the process of detection and community interaction. The causes of stigma are patriarchal culture in society, education level, age, gender, and social conditions. Keywords: